ASSESSING THE DG ECHO INDEX FOR HUMANITARIAN OPERATIONS AND CONTEXTUALISATION OF IT IN THE UKRAINIAN CRISIS: THE IMPACT OF RUSSIA’S WAR AGAINST UKRAINE (COMMENCED IN 2022) - Klymenko, Tatiana (Collection of scientific papers «ΛΌГOΣ», 2024)
The devastating war in Ukraine has created an unprecedented humanitarian crisis, demanding a multifaceted response from humanitarian organizations. The DG ECHO Index, a widely used tool for assessing the effectiveness of humanitarian operations, has faced scrutiny for its applicability in complex crises like this. This chapter focuses on the efficacy of the DG ECHO Index in the Ukrainian context, exploring its strengths, limitations, and potential for improvement.Through a mixed-methods approach, this chapter delves into the lived experiences of humanitarian practitioners, analyzing qualitative data from semi-structured interviews. Additionally, it examines quantitative data on humanitarian operations in Ukraine, aiming to assess the index’s effectiveness in capturing the nuances of complex crises.The chapter opens with a comprehensive overview of the DG ECHO Index, discussing its strengths and limitations. It then delves into the specific challenges posed by the Ukrainian crisis, highlighting the index’s applicability in a multi-actor environment with numerous humanitarian programs operating simultaneously.The chapter further analyzes the 2023 adaptation of the DG ECHO Index by the Bureau Of Population, Refugees, & Migration, exploring its potential to address the identified limitations. By examining the impact of this adaptation, the chapter ultimately aims to provide valuable insights and recommendations for improving humanitarian evaluation tools and enhancing their effectiveness in complex crisis contexts.Thischapter contributes to the ongoing dialogue on the efficacy of the DG ECHO Index and the development of more effective tools for assessing humanitarian operations. By providing evidence-based recommendations and practical insights, this chapter seeks to empower humanitarian organizations operating in Ukraine to refine their response and address the unique challenges presented by the crisis.The Chapter’s findings will be of interest to researchers, policymakers, humanitarian practitioners, and anyone concerned with improving the effectiveness of humanitarian response in complex crises like the war in Ukraine.